1987
DOI: 10.1029/jb092ib12p12507
|View full text |Cite
|
Sign up to set email alerts
|

Noble gases in diamonds: Occurrences of solarlike helium and neon

Abstract: Abstract. We have measured noble gases in 17 diamond samples, mostly inclusion free, from diverse, known locations. The 'He/'He ratios are characterized by a large spread

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…It is more akin to solar Ne. This important conclusion is now well established from recent precise Ne isotopic analyses on MORB (Sarda et al 1988, Marty 1989, Honda et al 1991, Hiyagon et al 1992) and on diamonds (Honda et al 1987, Ozima and Zashu 1988, 1991. The fact that the dissimilarity of the isotopic composition between the mantle and air is only seen in Ne supports the hypothesis Except for 78Kr, which is rare and therefore its measurement is very uncertain, mantle Kr is indistinguishable from atmospheric Kr.…”
Section: Noble Gas Constraintssupporting
confidence: 60%
“…It is more akin to solar Ne. This important conclusion is now well established from recent precise Ne isotopic analyses on MORB (Sarda et al 1988, Marty 1989, Honda et al 1991, Hiyagon et al 1992) and on diamonds (Honda et al 1987, Ozima and Zashu 1988, 1991. The fact that the dissimilarity of the isotopic composition between the mantle and air is only seen in Ne supports the hypothesis Except for 78Kr, which is rare and therefore its measurement is very uncertain, mantle Kr is indistinguishable from atmospheric Kr.…”
Section: Noble Gas Constraintssupporting
confidence: 60%
“…Gases interpreted to be from a primitive source in the Hawaiian islands also have values of -3.6 to -3.0%0 ( GERLACH and THOMAS, 1986). Recent work has suggested that a positive correlation may exist between 3He/4He and 6 r3C, with the heavier carbon isotopic composition being typical of primordial sources (HONDA et al, 1987). +,,, of the calcite is 0 to +2, similar to that for the silicate portion of the rock (Fig.…”
Section: Isotopic Composition Of the Calcite Segregationsmentioning
confidence: 66%
“…Assuming an upper limit given by the ReOs age of 3.52 Ga for peridotitic diamonds (Westerlund et al, 2006), although incompatible with N aggregation data, gives in situ produced 4 He concentrations higher than those measured in all the samples except for PEK013/4 where it would account for 41% of the total 4 He. At present it is not possible to determine whether the diamonds have quantitatively retained He (young coats) or experienced He loss by diffusion (ancient coats) although negligible He loss is most likely for diamond (Honda et al, 1987). From hereon, it is assumed that no major addition or loss of He has occurred, and that the He abundances and isotope ratios are representative of the fluid trapped at the time of coat crystallisation.…”
Section: Helium and Argon Isotopesmentioning
confidence: 97%